Building Internet Search Engines - Mustafa Akgül (Türk Kütüphaneciliği)
Internet search engines are powerful tools to find electronics objects such as addresses of individuals and institutions, documents, statistics of all kinds, dictionaries, catalogs, product information etc. This paper explains how to build and run some very common search engines on Unix platforms, so as to serve documents through the Web.